2021
DOI: 10.21203/rs.3.rs-242345/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Cognitive Decline using a Single-Channel EEG with an Interactive Assessment Tool

Abstract: BackgroundCognitive decline remains highly underdiagnosed despite efforts to find novel biomarkers for detection. EEG biomarkers based on machine learning may offer a noninvasive low-coast approach for identifying cognitive decline. However, most studies use multi-electrode systems which are less accessible. This study aims to evaluate the ability to extract cognitive decline biomarkers using a wearable single-channel EEG system with an interactive assessment tool.MethodsThis pilot study included data collecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Delta and VC9 activity decreased with the lower cognitive load that resulted from simulator trial repetition, but the theta band activity did not decrease. As shown in previous studies ( Maimon et al, 2020 ; Molcho et al, 2021 ), VC9 was found to be more sensitive to lower loads than theta and delta, as its activity also showed a significant decrease between the first and third task trials. This further validates VC9 as an effective biological measurement for the assessment of cognitive load while performing laparoscopic tasks using the surgical simulator specifically and suggests that it may provide a measure of cognitive functioning during surgery.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Delta and VC9 activity decreased with the lower cognitive load that resulted from simulator trial repetition, but the theta band activity did not decrease. As shown in previous studies ( Maimon et al, 2020 ; Molcho et al, 2021 ), VC9 was found to be more sensitive to lower loads than theta and delta, as its activity also showed a significant decrease between the first and third task trials. This further validates VC9 as an effective biological measurement for the assessment of cognitive load while performing laparoscopic tasks using the surgical simulator specifically and suggests that it may provide a measure of cognitive functioning during surgery.…”
Section: Discussionsupporting
confidence: 72%
“…A single-channel EEG device utilizing decomposition of the EEG signal via harmonic analysis was used to obtain the novel VC9 biomarker as well as the frequently used theta and delta bands. All EEG features (i.e., theta, delta, and VC9) were previously shown to correlate with cognitive load levels ( Antonenko et al, 2010 ; Maimon et al, 2020 ; Bolton et al, 2021 ; Molcho et al, 2021 ). Experiment 1 consisted of three repeating trials on the surgery simulator, and its results showed that participants’ performances improved while VC9 and delta activity decreased.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations